2006
DOI: 10.1207/s15327590ijhc2001_3
|View full text |Cite
|
Sign up to set email alerts
|

Interruption Management and Telephone Call Screening

Abstract: Notification-oriented computer interfaces are growing in importance, as is our understanding of how users manage interruptions. To gain insights relevant to the design of such interfaces, this study explored telephone call screening as a common example of how people manage technology-driven interruptions in their everyday residential environment. Survey results showed that audio screening is a frequent and regular practice, often used as part of an active, multicue strategy for managing interruptions. Frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…Therefore, the subjective interruptibility of a worker is affected by the cognitive cost of the interruption. For instance, the cognitive cost of an interruption is lower and subjective interruptibility is higher at task breakpoints (Iqbal & Bailey, 2005, 2006.…”
Section: Interruptibility Measure Incorporating Head Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the subjective interruptibility of a worker is affected by the cognitive cost of the interruption. For instance, the cognitive cost of an interruption is lower and subjective interruptibility is higher at task breakpoints (Iqbal & Bailey, 2005, 2006.…”
Section: Interruptibility Measure Incorporating Head Motionmentioning
confidence: 99%
“…These techniques include PC operationbased methods, which typically rely on counting keystrokes or mouse clicks (Honda et al, 1997;Minakuchi, Takeuchi, Kuramoto, Shibuya, & Tsujino, 2004), and sensor-based methods, which involve sensors that detect conversations or events (Danninger & Stiefelhagen, 2008;Forgaty et al, 2005;Milewski, 2006). However, the features utilized in the previous studies do not necessarily reflect intellectual activities that do not have observable outputs.…”
Section: Introductionmentioning
confidence: 99%
“…There has been widespread adoption of answering machines, caller ID, and voicemail, and the majority of adults surveyed in 1999 admitted to screening calls. 4 In addition, mobile telephones are replacing land lines, with 90% of Americans having a cell phone in 2014 5 and about 41% of US households having only wireless phones in 2013. 6 Texting is also replacing conversation and voicemail, 7 a transition that began a shortly before our study.…”
Section: P Ediatric Research In Office Settings (Pros)mentioning
confidence: 99%
“…A large body of research has shown that users' performances on a wide variety of ongoing tasks are often seriously disrupted by interruptions [1] [5] [22]. Interruptions are common in any technical organization, in part because the work of individual team members is highly interdependent.…”
Section: Figure 1 Common Working Hoursmentioning
confidence: 99%